Penerapan Ice Breaking Sebagai Stimulus Minat Belajar Peserta Didik di SDN 04 Kubang Putiah - Rahmadani, Siska; Dewi, Puti Andam; Putri, Yani Mukminah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research refers to students' lack of interest in learning in the learning process. Where the learning carried out tends to use old methods. This is also due to the lack of creativity and interesting innovation in learning, so that students easily feel bored when studying and this has an impact on students' interest and enthusiasm for learning in receiving learning materials. One solution that can be applied to stimulate students' interest in learning again is by thawing the atmosphere during learning, such as implementing the ice breaker